(untitled) (Colombia Medica, 1986)
The World Health Organization has promoted investigations on the prevalence of neurological diseases in several countries. Especial protocols for persons under 7 years old and those who are 7 and older were designed. The study must be done in two stages; in the first, a pilot test will cover 1000 people, and the second will assess 25000 persons. We are reporting in this paper the results of the initial phase from Jamundí, Valle, Colombia. Findings from the pilot study show that migraine and epilepsy are the most common neurological diseases in this community.